Confirmatory factor analysis of Adolescent’s School Engagement Scale (ASES) - Sánchez Hernández, María Enriqueta (2020)
School involvement includes the behaviors, beliefs and emotions of student population have towards their school activity, it is a construct that has been widely studied in college students but infrequently in middle school students. Adolescents that are more engaged in school activities demonstrate better performance in class and are less prone to get involved in risk behaviors, which is why a more in-depth study is needed. The objective of this article is to present the psychometric properties of an instrument to evaluate students' school engagement at secondary school level. This quantitative research was carried out with students from Mexico and the data were obtained between 2018 and 2019. The non-probabilistic sample consisted of 503 public high school students from the City of Xalapa, Veracruz; 57.5% were women and 42.5% men, aged between 11 and 15 years (M = 13.12, D.E. 0.92).The final version of the scale contains ten items, each with seven possible responses which evaluates 3 dimensions: behavioral, emotional and cognitive. The confirmatory factor analysis showed adequate goodness of fit indexes CFI = 0.98, TLI = 0.98, SRMR = 0.03, RMSEA = 0.05 and the coefficients of reliability were α = 0.88 y λ2 = 0.88. The results indicate that the ASES is a suitable instrument to evaluate early adolescence school involvement.